Avaliação econômica de três tipos de suplementação mineral para bovinos de corte no Estado do Pará - BARBOSA, Francisberto Batista (Universidade Federal do Pará, 2017)
Three alternatives of mineral supplementation of 18 to 20-month-old male Nelore cattle with 299.5 to 308.5 kg of body weight were used at a farm in northeast of Pará state, Brazil. To evaluate which mineral mixture resulted in better cost-benefit, three groups of 20 head were supplemented for six months, from March to August of 2012. Group 1 was supplemented with a selected mineral mixture (SMM) composed of 25kg NaCl, 50kg dicalcium phosphate, 190g copper sulphate, 60g cobalt sulphate, and 15g sodium selenite, having 133g Na, 123g P, 631mg Cu, 167mg Co, and 9mg Se per kg; this mixture was made based in previous clinical-nutritional examination of herd. Group 2 (control), supplemented only with NaCl; and group 3 received a commercial mineral mixture (CMM), routinely used in this farm, with 130g P, 220g Ca, 18g Mg, 36g S, 6000mg Zn, 1500mg Cu, 2000mg Mn, 200mg Co, 90mg I, and 36mg Se per kg. Concentrations of phosphorus, copper, zinc and iron were determined in liver and 12th ribs. The best cost-benefit alternative was the SMM; the forage alone did not contain enough Co to meet the requirements of the control group, but provided enough P, Cu, Zn and Se during the five months of the experiment.